FOREIGN CONVICTS EXECUTION: CRIMINAL JURISDICTION BENEATH INTERNATIONAL TENSION - Tajudin Tajudin; Solihin Niar Ramadhan (Faculty of Law, Universitas Sebelas Maret, 2016)
AbstractThe existence ofthe death penalty remains a controversial issue in several countries around the world. Although many countries have abolished the death penalty in its criminal law system, Indonesia still retainsthe capital punishment within its criminal law policy.In Practice, theexecutionhasbeen implemented long agodespite the fact that it leaves a lot of problems. There are many reactions from other countries when prosecutors process to execute foreign nationals. On fact, many head of state request to president of Republic of Indonesia to change the punishment or give forgiveness.This journal will discuss the main problemsencountered in the implementation of the death penalty in Indonesia. The problems are: Firstly,the imposition of the death penalty for foreign nationals in order to implement the national jurisdiction underinternational community’s pressure. Secondly,the postponement of death sentence associated with the theory of retribution and human rights.